The thin red line - Malick, Terrence,|d1943.; Geisler, Robert Michael; Roberdeau, John.; Twentieth Century Fox.; Phoenix Pictures; Fox 2000 Pictures; Viva Video (Beverly Hills, Calif. 20th Century Fox Home Entertainment ; distributed in the Philippines by Viva Video, 1999)
World War II battle between the Japanese and the American military forces for control of the strategic island of Guadalcanal.
Originally released as a motion picture in 1998.
Based upon the novel by James Jones.
Director of photography, John Toll ; production designer, Jack Fisk ; edited by Billy Weber, Leslie Jones, Saar Klein ; music by Hans Zimmer.
Sean Penn, Adrien Brody, Jim Caviezel, Ben Chaplin, George Clooney, John Cusack, Woody Harrelson, Elias Koteas, Jared Leto, Dash Mihok, Tim Blake Nelson, Nick Nolte, John C. Reilly, Larry Romano, John Savage, John Travolta, Arie Verveen.
VCD
Keywords: Guadalcanal, Battle of, Solomon Islands, 1942-1943.; World War, 1939-1945 -- Drama